Exploration of Career Differences in Career Interests of Students with Special Needs - Heiriyah, Ainun; Haryadi, Rudi (Universitas Islam Negeri Raden Intan Lampung, 2019)
This study aims to analyze and identify trends in the career interests of students with special needs in the city of Banjarmasin and see if there are differences in career interest trends between students with special needs in primary and secondary schools. The research design used was a cross-sectional survey. The results show that there are differences in career interests of students with special needs related to the field of Social careers, Realistic career fields, Artistic career fields, Conventional career fields, Enterprising career fields, and Investigative career fields. Also, there was a small difference in career interest scores between elementary and middle school students, even though overall, the trend for interests was almost the same. Based on the research results obtained, it is recommended to further researchers to conduct further research on career interests for students with special needs with more specific characteristics and develop assessment instruments that are more relevant for students with special needs.